Young Investor’s Investment Decision Making: The Influence of Heuristic Behavior, Risk Perception, and Herding Bias - Ayu Oktaviani; Nor Mawaddah (Universitas Negeri Malang, 2024)
Purpose:Theory of Behavioral Finance assumes that there are various things inherent in humans such as emotions, interests, and traits that make them unable to make rational decisions. This study aims to analyze and find out what kind of impact heuristic behavior, risk perception, and herding bias have on investment decision making by young investors.Method:This research is a quantitative study with students at the Faculty of Economics and Business, Lambung Mangkurat University who are or have invested on the Indonesia Stock Exchange as the sample of this study. The research data comes from primary data processed using multiple linear regression analysis.Findings:The findings of this study successfully prove that there is an influence of heuristic behavior, risk perception, and herding bias on investment decisions by young investors.Originality/Value:This study uses students of the Faculty of Economics and Business, Lambung Mangkurat University as a research sample who belong to generation Z with a tendency to have higher emotions and egos, making it difficult to make investment decisions.